(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This study analyzed the hypothesized choices between ENEM results contingent upon pro- -study responses and concurrent responses to these results by 30 students in the three high school degrees in private and public high schools. The points were presented in dyads and ranged from 400 to 1000 points in seven conditions. The highest points were contingent to study responses, and the lowest points were contingent on concurrent responses to the study. Lower points contingents to study responses were correlated to higher frequencies of choices for concurrent behavior and lowest points. The data showed a greater discount in public schools than in private schools. Students of first year (youngest) had deepest discount of all participants. These data corroborate the findings of the literature area.